Expanding access to evidence-based psychotherapy in VA settings: implementation of the brief cognitive behavioral therapy for depression program - Mignogna, Joseph; Boykin, Derrecka; Gonzalez, Raquel D.; Robinson, Andrew; Zeno, Darrell; Sansgiry, Shubhada; Broderick-Mcdaniel, Jennifer; Roberson, Richard B.; Sorocco, Kristen; Cully, Jeffrey A. (Frontiers in Health Services, 2023)
Introduction: Evidence-based psychotherapies (EBPs) are effective for mental health conditions, but access to these services remains limited and rural Veterans are particularly underserved. Specialized implementation and dissemination programs are needed to improve access to known EBPs. Methods: The current project sought to improve access to a known EBP – brief cognitive behavioral therapy for depression (Brief CBT). Diverse Veterans and those from rural settings were a focus of this work. Aligned with the RE-AIM framework, a multifaceted implementation program was used to train and support VHA providers in their use of Brief CBT in VHA mental health settings, with specific outreach efforts made to providers at VHA Community-Based Outpatient Clinics (CBOCs) where rural Veterans often receive care. Evaluation included all facets of RE-AIM with a particular focus on adoption, effectiveness, and maintenance. Results: During the first two years, over 40 VHA facilities adopted the program across four regional networks. Eighty-three providers were approached, and 54 (65.1%) providers completed the training and are delivering the intervention. A total of 688 Veterans, 174 rural (25.7%), received 2,186 sessions (average of 3.5 sessions per Veteran). Veterans receiving Brief CBT with elevated depression scores who completed three or more sessions were found to have significant symptom reductions of 4.6 points (first to last available evaluations). Discussion: Implementation efforts of Brief CBT resulted in rapid uptake and significant clinical impact on Veterans. Rural outreach efforts, including targeted training for CBOC providers and use of tele-mental health, enhanced availability of EBP services for rural Veterans.